Just4Us: Development of a Counselor-Navigator and Text Message Intervention to Promote PrEP Uptake Among Cisgender Women at Elevated Risk for HIV. (6th March 2021) - Teitelman, Anne M.; Koblin, Beryl A.; Brawner, Bridgette M.; Davis, Annet; Darlington, Caroline; Lipsky, Rachele K.; Iwu, Emilia; Bond, Keosha T.; Westover, Julie; Fiore, Danielle; Tieu, Hong-Van
Abstract: In the United States, pre-exposure prophylaxis (PrEP) uptake among eligible cisgender women has been slow, despite the availability of oral PrEP since 2012. Although women make up nearly 20% of those living with HIV, there are currently few PrEP uptake interventions for cisgender women at elevated risk for acquiring HIV. Here we describe the process used to design and pre-pilot test Just4Us, a theory-based behavioral intervention to promote PrEP initiation and adherence among PrEP-eligible cisgender women. This work was part of a multiphase study conducted in New York City and Philadelphia, two locations with HIV rates higher than the national average. The counselor-navigator component of the intervention was designed to be delivered in a 60- to 90-min in-person session in the community, followed by several phone calls to support linkage to care. An automated text messaging program was also designed for adherence support. Just4Us addressed personal and structural barriers to PrEP uptake using an empowerment framework by building on women's insights and resources to overcome barriers along the PrEP cascade. Usability pre-pilot testing results were favorable and provided valuable feedback used to refine the intervention.